Synthesis and Crystal Structure New Zn(II) Coordination Polymer with 4-Connected sql Tetragonal Plane Net - Zhang, Shuxin (Asian Journal of Chemistry, 2014)
A new coordination polymer {[Zn(5-NO2-ip)(bimb)]·H2O}n (1) with 5-nitro-1,3- benzenedicarboxylic acid (5-NO2-ip) and 1,4-bis(1-imidazol-yl)-2,5-dimethyl benzene (bimb) has been prepared by hydrothermal synthesis and characterized by single-crystal X-ray diffraction and EA. Complex, {[Zn(5-NO2-ip)(bimb)]·H2O}n (1), is triclinic, space group P-1 with a = 9.094 (2) , b = 9.428 (4), c = 13.999 (3) Å, a = 71.553 (6) °, b = 87.530 (6)°, g = 84.220 (7) °, V = 1132.7 (6) Å3, Z = 2, Mr = 530.79, Dc = 1.556 g/cm3 and F(000) = 544. The final refinement gave R = 0.0416 and wR = 0.1102 for 4125 reflections with I > 2s (I). X-ray diffraction analysis reveals that the complex 1 displays a two-dimensional structure with 4-connected sql topology.